1999
DOI: 10.1210/jc.84.1.216
|View full text |Cite
|
Sign up to set email alerts
|

MEN1 Gene Analysis in Sporadic Adrenocortical Neoplasms

Abstract: Adrenocortical tumors occur as sporadic tumors, as part of the multiple endocrine neoplasia type 1 (MEN1) syndrome or as part of other hereditary disorders. We recently cloned the MEN1 gene, a tumor-suppressor gene located on chromosome 11q13. Subsequently, we showed that sequential somatic inactivation of both alleles of the MEN1 gene contributes to the development of some sporadic endocrine neoplasms (parathyroid, enteropancreatic neuroendocrine, bronchial carcinoid, and pituitary tumors). We now studied whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 0 publications
0
35
0
3
Order By: Relevance
“…Allelotyping analysis of her adrenal tumor showed LOH for all informative markers at 11q13. Genetic analyses in sporadic adrenal carcinomas have shown that more than 60% exhibit LOH at 11q13 (28, 33 -37), but these tumors rarely harbor MEN-1 gene mutation (, 7%) (33, 35 -37) and they have normal MEN-1 gene expression (33,34), supporting the involvement of a TSG at 11q13, distinct from MEN-1, in the pathogenesis of adrenal carcinomas (36). Taken together, these data suggested that patient I:2 presented a sporadic adrenocortical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Allelotyping analysis of her adrenal tumor showed LOH for all informative markers at 11q13. Genetic analyses in sporadic adrenal carcinomas have shown that more than 60% exhibit LOH at 11q13 (28, 33 -37), but these tumors rarely harbor MEN-1 gene mutation (, 7%) (33, 35 -37) and they have normal MEN-1 gene expression (33,34), supporting the involvement of a TSG at 11q13, distinct from MEN-1, in the pathogenesis of adrenal carcinomas (36). Taken together, these data suggested that patient I:2 presented a sporadic adrenocortical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperplasia is typically found in MEN 1 patients presenting ACTH hypersecretion (Cushing's disease), whereas ACC has rarely been reported in MEN 1 patients. Somatic mutation of the menin gene is very rare: one mutation was identified in a series of 41 AAs in one study (24) and one mutation in a series of ACCs was found in another (25). By contrast, LOH at 11q13 was identified in more than 90% of informative ACC in three different series whereas it has been reported in fewer than 20% of informative adenomas (23 -25).…”
Section: Menin Gene and Locus 11q13mentioning
confidence: 99%
“…Losses were observed at 1p, 17p, 22p, 22q, 2q and 11q in up to 62% of cases of ACC (22). Studies using microsatellite markers have demonstrated high percentages of loss of heterozygosity (LOH)/allelic imbalance at 11q13 (100%) (23)(24)(25) and 2p16 (92%) (23) in carcinomas. Moreover, LOH of the 17p13 locus (26,27) has been reported to be highly specific to malignant tumours and to be of prognostic value for the recurrence of localized tumours (28).…”
Section: The Importance Of Genetic Alterations In Sporadic Actsmentioning
confidence: 99%
“…Genomic instability is the basis of gross chromosomal alterations and aneuploidy (Giordano et al, 2009). Most cases of adrenocortical cancers appear to be sporadic and only a small percentage of patients present ACC as a component of one of the known hereditary cancer syndromes, such as the Li-Fraumeni's syndrome, the Beckwith-Wiedemann syndrome or the Multiple Endocrine Neoplasia type 1 (Koch et al, 2002;Sidhu et al, 2004;Libé & Bertherat, 2005;Kjellman et al, 1999;Schulte et al, 2000;Heppner et al, 1999). One important difference between these two forms of adrenocortical carcinomas (either sporadic or part of an hereditary syndrome) is the current degree of knowledge about its tumorigenesis (Soon et al, 2008).…”
Section: Adrenal Cortex Cancermentioning
confidence: 99%
“…This gene is also a tumor suppressor gene and it is located in chromosome 11 (11q13). LOH at 11q13 exist in more than 90% of ACC (Kjellman et al, 1999;Schulte et al, 2000;Heppner et al, 1999) Adapted from Soon P. et al, (2008). Molecular markers and the pathogenesis of adrenocortical cancer.…”
mentioning
confidence: 99%